Penyelidikan Fasies dan Lingkungan Pengendapan pada Singkapan Batuan Karbonat Berdasarkan Karakteristik dan Ichnofasies di Sungai Oyo, Kecamatan Wonosari, Kabupaten Gunung Kidul, DIY - Timotius Tuska, Robert; Putri, Dwiginasa; Angga Purnama, Wahyu; Abdillah Ahmad, Ghani; Flowers Rizqi, Al Hussein (ReTII, 2024)
Research on Facies and Environment The deposition of carbonate rocks of the Oyo Formation is located on the Oyo River, Wonosari District, Gunung Kidul Regency, Special Region of Yogyakarta with a geographical position of 7Â°54’45.7"S and 110Â°36’38.9"E. The aim of this research is to identify facies and depositional environments through research methods from outcrop profile (MS) methods and rock descriptions. The results of the rock description show that the rocks are in the form of grainstone and wackestone with a depositional environment in the form of a sublittoral zone. The research area is divided into 4 stations, each station has a variety of rocks in the form of carbonate rocks. Only a little research has been carried out in this area, this is a stage to develop more in-depth research regarding the Oyo Formation in this area.